Clomiphene citrate versus high doses of gonadotropins for in vitro fertilisation in women with compromised ovarian reserve: a randomised controlled non-inferiority trial - Ragni Guido; Levi-Setti Paolo E; Fadini Rubens; Brigante Claudio; Scarduelli Claudia; Alagna Federica; Arfuso Veronica; Mignini-Renzini Mario; Candiani Massimo; Paffoni Alessio; Somigliana Edgardo (Reproductive Biology and Endocrinology, 2012)
Abstract Background The aim of the present randomised controlled non-inferiority trial is to test whether in women with compromised ovarian reserve requiring in vitro fertilisation, a protocol of ovarian stimulation using exclusively clomiphene citrate performs similarly to a regimen with high doses of gonadotropins. Methods Women with day 3 serum FSH > 12 IU/ml on at least two occasions or previous poor response to hyper-stimulation were recruited at four Italian infertility units. Selected women were allocated to clomiphene citrate 150 mg/day from day 3 to day 7 of the cycle (n=145) or to a short protocol with GnRH agonist 0.1 mg and recombinant FSH 450 IU daily (n=146). They were randomised by means of a computer-generated list into two groups. The study was not blinded. The main outcome of the study was the delivery rate per started cycle. Results The study was interrupted after the scheduled two years of recruitment before reaching the sample size. 148 women were allocated to clomiphene citrate and 156 to the short protocol with high doses of gonadotropins; 124 and 125 participants were analysed in the groups, respectively. Women allocated to high doses of gonadotropins retrieved more oocytes and had a higher probability to perform embryo-transfer. However, the chances of success were similar. The delivery rate per started cycle in women receiving clomiphene citrate and high-dose gonadotropins was 3% (n=5) and 5% (n=7), respectively (p=0.77). The mean estimated cost per delivery in the two groups was 81,294 and 113,107 Euros, respectively. No side-effects or adverse events were observed. Conclusions In women with compromised ovarian reserve selected for in vitro fertilisation, ovarian stimulation with clomiphene citrate or high-dose gonadotropins led to similar chances of pregnancy but the former is less expensive. Trial registration Trial registered on http://www.clinicaltrials.gov (NCT01389713)